Barbados : Fourth Review Under the Extended Arrangement, Requests for Augmentation of Access, and Modification of Performance Criteria-Press Release; Staff Report; and Statement by the Executive Director for Barbados. (IMF Staff Country Reports; Country Report ;, 2020)
Barbados has made good progress in implementing its Economic Recovery and Transformation (BERT) plan to restore fiscal and debt sustainability, rebuild reserves, and increase growth-but faces major challenges owing to the global coronavirus pandemic. Since May 2018, international reserves have increased from a low of USD 220 million (5-6 weeks of import coverage) to more than USD 1 billion at end-October 2020. This, and a successful 2018-19 public debt restructuring, have helped rebuild confidence in the country's macroeconomic framework. While the local spread of COVID-19 has been successfully contained, allowing for a cautious reopening of the tourism sector in July, economic activity remains severely depressed owing to the global pandemic. Risks to the outlook remain elevated.